Strategi Pemasaran Brand Rock Our Soul dalam Penjualan di Media Sosial Instagram - Purba, Boy Randy; Khairullah, Khairullah (Mahesa Research Center, 2025)
The development of digital technology has changed marketing strategies, especially through social media such as Instagram. Rock Our Soul, an accessories brand with dark fashion, gothic, and streetwear styles, leverages Instagram to build brand identity and increase customer engagement. This research aims to analyze Rock Our Soul's marketing strategy in increasing sales and interaction with customers on Instagram. Using a qualitative approach, data was collected through observation of Instagram uploads, interviews with account managers, and analysis of customer interactions. The results show that the combination of strong visual aesthetics, direct selling strategies through Direct Messages, and involvement in offline events and digital communities increases brand awareness and customer loyalty. Rock Our Soul also implements sales hooks and experience-based strategies to increase sales conversions. This study provides insights for other brands in optimizing social media as the main marketing tool in the digital era.